Increased Magnetic Susceptibility in the Deep Gray Matter Nuclei of Wilson's Disease: Have We Been Ignoring Atrophy? - Jing, Xiao-Zhong; Yuan, Xiang-Zhen; Li, Gai-Ying; Chen, Jia-Lin; Wu, Rong; Yang, Ling-Li; Zhang, Shu-Yun; Wang, Xiao-Ping; Li, Jian-Qi (Frontiers in Neuroscience, 2022)
Background: Histopathological studies in Wilson’s disease (WD) have revealed increased copper and iron concentrations in the deep gray matter nuclei. However, the commonly used mean bulk susceptibility only reflect the regional metal concentration rather than the total metal content, and regional atrophy may affect the assessment of mean bulk susceptibility. Our study aimed to quantitatively assess the changes of metal concentration and total metal content in deep gray matter nuclei by quantitative susceptibility mapping to distinguish neurological and hepatic WD patients from healthy controls. Methods: Quantitative susceptibility maps were obtained from 20 neurological WD patients, 10 hepatic WD patients, and 25 healthy controls on a 3T magnetic resonance imaging system. Mean bulk susceptibility, volumes and total susceptibility of deep gray matter nuclei in different groups were compared using a linear regression model. The area under curve (AUC) was calculated by receiver characteristic curve to analyze the diagnostic capability of mean bulk susceptibility and total susceptibility. Results: Mean bulk susceptibility and total susceptibility of multiple deep gray matter nuclei in WD patients were higher than those in healthy controls. Compared with hepatic WD patients, neurological WD patients had higher mean bulk susceptibility but similar total susceptibility in the head of the caudate nucleus, globus pallidus, and putamen. Mean bulk susceptibility of putamen demonstrated the best diagnostic capability for neurological WD patients, the AUC was 1, and the sensitivity and specificity were all equal to 1. Total susceptibility of pontine tegmentum was most significant for the diagnosis of hepatic WD patients, the AUC was 0.848, and the sensitivity and specificity were 0.7 and 0.96, respectively. Conclusions: Brain atrophy may affect the assessment of mean bulk susceptibility in the deep gray matter nuclei of WD patients, and total susceptibility should be an additional metric for total metal content assessment. Mean bulk susceptibility and total susceptibility of deep gray matter nuclei may be helpful for the early diagnosis of WD.